The art of Printmaking from the Quest to find I-san Identity - สังวรดี, อานนท์ (Journal of Fine and Applied Arts Khon Kaen University, 2018)
"East" refers to the territory of northeastern Thailand. The search for identity issues in the Northeast. There are many dimensions in terms of social, political, economic, cultural, educational values. This diversity is an interesting starting point in the search for the meaning of the word. "I-San identity" from the many dimensions and diversity mentioned above. The creator has framed the concept of seasonal weather. The terrain is located at the equatorial zone with high temperatures almost all year round. Heat, drought, variability cause surface traces, reflecting the beauty of the hardships. It transforms into aesthetics, a way of life that creates a cultural tradition that is deeply connected to nature. Until it has become a valuable identity, it has been inherited to the present. I-San people have respect Faith in nature deeply It has easy-to-eat features. That does not mean that the rough way of life. But if it means intelligently adjusting to the environment. And in this simplicity itself. Another role is to make I-san people associated with religion, agriculture, animal husbandry. And the season is important. From the content of such a clear identity has led to the creative process of graphic arts. By using time and environment cues, such as bark clay, to create in the work by harmonizing the lines that bind into shapes, weights, shapes, surfaces, dimensions and space. The symbolic meaning of farmers, buffaloes, beetles, animals, with the technique of printing, material and imprints of trenches.